EVALUATION OF SERUM TOLL-LIKE RECEPTOR 4 AND NUCLEAR FACTOR-ΚBP65 PROTEINS IN ORAL SQUAMOUS CELL CARCINOMA - Sathiyamoorthy, Jayalalitha; Shyamsundar, Vidyarani; Babu, N. Aravindha; Shanmugam, Subbaih; G. Mani, Jagadeesan.; Chinnaiyan, Ponnuraja; Hari, Rajeswary (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study is aimed to estimate the serum toll-like receptor 4 (sTLR 4) and nuclear factor-κB (NF-κB) p65 proteins in patients of oral squamous cell carcinoma (OSCC). Methods: The study was performed in prospective cases of 22 OSCC patients, 10 oral epithelial dysplasia patients, 8 control with chewing habits, and 4 control patients. The estimation of sTLR 4 and NF-κBp65 proteins was done by enzyme-linked immunosorbent assay method. The Pearson correlation test was performed to find out the relationship between these two proteins. Results: There was an increase in the sTLR 4 protein level in study groups OSCC, oral premalignant disorders, control with chewing habits, and control habits such as 1.31 ng/ml±1.06 ng/ml, 1.99 ng/ml±0.98 ng/ml, and 2.11 ng/ml±0.61 ng/ml, respectively, when comparable (p=0.008) to control patients with 0.60 ng/ml±0.24 ng/ml. However, in the case of serum level NF-κBp65 protein all the study groups including the control showed same values. The Pearson correlation test showed significant relationship (rpearson=0.91, [p<0.0005]) of these two proteins only in the OSCC patients. Conclusion: It can be concluded that serum levels of TLR 4 are increased in OSCC patients, but there was no variation seen for the NF-κBp65 protein. There is a strong interrelationship exist between the serum levels of TLR 4 and NF-κBp65 proteins in the OSCC patients only.